Identifying and Prioritizing Agility Drivers Using FTOPSISAnd Fractional Programming Approach - Behnam Molavi; Majid Esmaelian; Reza Ansari (چشم‌انداز مدیریت صنعتی, 2012)
The firststepin order to achieveorganizationalagility is identification of changes and pressures from business environment, whichactasdrivingforces and lead to adoption of agility strategy in organization. Proposed models in the literature have disadvantage of the lack of scientific and coherent method to identify driving forces of agility. This paper, therefore, seeks to present a method for identifying and ranking the driving forces of agility by multi-criteria decision making techniques. The paper draws on a broad literature review to identify driving forces of agility and their evaluation criteria. Then, the literature findings developed with respondents’ contextualized practical experience. In the next stage, by combination of expert experience and fuzzy ENTROPY Weight of criteria are determined. Finally by use of FTOPSIS and fractional programming the Agility Drivers has been Prioritizing.